Asking “How” and “Why” and “Under What Conditions” Questions: Using Critical Realism to Study Learning and Teaching - Miller-Young, Janice (Teaching and Learning Inquiry, 2025)
Research paradigms offer a way for scholars to design, communicate, and reflect on their research effectively. A paradigm encapsulates the researcher’s worldview, including the epistemology, ontology, and axiology of the research. Researchers are often initiated, whether explicitly or implicitly, into particular paradigms through graduate study. This can cause difficulties in the multidisciplinary landscape of SoTL where practitioners either have to learn a new domain and/or communicate to peers outside their discipline. Learning about common research paradigms can help address these challenges. Four commonly used paradigms that have been proposed as relevant for SoTL research are post-positivist, critical realist, interpretive, and transformative (including indigenous). This article describes the basic tenets of critical realism and discusses them in relation to SoTL research. It i) describes key concepts within critical realism, including a stratified reality and a focus on causal mechanisms and the relationship between structure and agency, ii) explains how critical realism can be applied to studying learning and what this means for choice of SoTL methodology and method, and iii) describes the key aspects of two published SoTL studies. The paper concludes by suggesting that critical realism can enhance the theoretical rigor, practical utility, and interdisciplinarity of SoTL research.